The relationship between adolescents’ physical activity, circadian rhythms, and sleep - Liu, Daoli; He, Jin; Li, Hengfen (Frontiers in Psychiatry, 2024)
】 Objective: To explore the correlation between physical activity, circadian rhythms, and sleep in adolescents, and analyze the influencing factors of sleep quality in this population.Methods: A total of 381 high school students were selected through cluster sampling in a specific high school. The Pittsburgh Sleep Quality Index (PSQI) was employed to categorize the participants into a good sleep quality group (n=199) and a poor sleep quality group (n=182). Comprehensive assessments were conducted using the Hamilton Depression Rating Scale (HAMD), Hamilton Anxiety Rating Scale (HAMA), PSQI, Morningness-Eveningness Questionnaire-5 (MEQ-5), and International Physical Activity Questionnaire Short Form (IPAQ-SF).Results: The prevalence of poor sleep quality is 47.8%. The BMI in the poor sleep quality group is higher than that in the good sleep quality group, and the male ratio is lower than that in the good sleep quality group. The poor sleep quality group exhibits significantly higher levels of depression, anxiety, evening chronotype, and low physical activity compared to the good sleep quality group.Spearman rank correlation analysis revealed a positive correlation between the PSQI total score and HAMA and HAMD scores, and a negative correlation with physical activity and MEQ-5 scores. Binary logistic stepwise regression analysis identified lack of physical activity, eveningness chronotype, anxiety, and depression as risk factors for poor sleep quality.: Adolescent sleep quality is correlated with gender, BMI, anxiety, depression, chronotype, and physical activity levels. The findings highlight the importance of considering these factors in interventions aimed at improving sleep health in adolescents.